El bordado en la indumentaria étnica masculina del curso alto del río Cañar (Ecuador) - López y Sebastián, Lorenzo E. (Revista Española de Antropología Americana, 2003)
This paper studies some pieces of male clothing from Cañari Indians, Ecuador, with special mentions to embroidery techniques, designs, and colors of decorative elements. Pieces are described, and related to the use of ethnic clothing as an element of cultural differentiation in modern society.